PENGEMBANGAN MEDIA PAPAN PERKALIAN 3D BERBASIS GAMIFIKASI PADA MATERI PERKALIAN KELAS II SEKOLAH DASAR - Nur Latifatun Nikmah; Sugeng Eko Putro Widoyoko; Arum Ratnaningsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to: 1) Produce a product in the form of Gamification-Based 3D Multiplication Board Media on Multiplication Material for Grade II Elementary School. 2) Knowing the feasibility of Gamification-Based 3D Multiplication Board Media on Multiplication Materials for Grade II Elementary School. This research is a type of Research and Development (RnD) using the ADDIE model which has 5 stages of development namely Analyze, Design, Development, Implementation, and Evaluation. The research subjects were grade II students of SD Negeri Bringin in the 2024/2025 school year with a total of 28 students. Data collection techniques are observation, interview, questionnaire, and test. Data analysis is feasibility analysis, practicality analysis, and effectiveness analysis. The results of this study are: 1) Gamification-based 3D Multiplication Board Media on Multiplication Materials for Grade II Elementary School. 2) The results of product validation obtained an average score of 3.42 with the qualification “Very Feasible”, the results of practicality 3.84 with the qualification “Very Practical”, the results of effectiveness 0.80 with the qualification “Effective”. Based on this study, it can be concluded that the Gamification-Based 3D Multiplication Board Media on Multiplication Material for Grade II Elementary School is suitable for use as learning media in elementary schools.